Photophysics of a Ruthenium Complex with a π-Extended Dipyridophenazine Ligand for DNA Quadruplex Labeling - Schindler, Julian; Traber, Philipp; Zedler, Linda; Zhang, Ying; Lefebvre, Jean-Francois; Kupfer, Stephan; Gräfe, Stefanie; Demeunynck, Martine; Chavarot-Kerlidou, Murielle; Dietzek, Benjamin (Journal of Physical Chemistry A, 2018)
The light-switch mechanism of the complex [Ru(bpy)2(Br-dpqp)](PF6)2 (1, bpy = 2,2′-bipyridine, Br-dpqp = 12-bromo-14-ethoxydipyrido[3,2-a:2′,3′-c]quinolino[3,2-h]phenazine), i.e., a light-up probe for the selective labeling of G-quadruplexes, is investigated by time-resolved transient absorption and emission spectroscopy. We show that, in contrast to the prototypical light-switch complex [Ru(bpy)2(dppz)](PF6)2 (2, dppz = dipyrido[3,2-a:2′,3′-c]phenazine), a 3ππ∗ state localized on the π-extended ligand is the state determining the excited-state properties in both protic and aprotic environments. In aprotic environments, emission originates from a bright 3MLCTphen state, which is thermally accessible from the 3ππ∗ state at ambient temperature. In the presence of water, i.e., in environments resembling in cellulo situations, the thermally accessible 3MLCT state is altered and becomes close in energy to the 3ππ∗ state, which induces a rapid excited-state deactivation of the 3ππ∗ state and a comparably weak emission.
CRIS-Team Scopus Importer:2023-04-20